Strategies of the treatment of spontaneous esophageal rupture: Report of thirteen cases from Xingtai, Hebei Province, China - Yonghui, Di (Asian Journal of Medical Sciences, 2016)
Aims and Objectives: To explore the treatment of spontaneous esophageal rupture. Materials and Methods: The treatments of thirteen patients hospitalized with spontaneous esophageal rupture were analyzed retrospectively. Initially three cases of hospitalized patients were given operative treatments. During the surgery, food residue and necrotic tissue were removed, and repair of esophageal rupture and jejunostomy were implemented. One closed chest drainage tube was placed at the end of the surgery. All the patients were given nutritional support through vein and nutrient canal placed into the jejunum. The remaining ten cases were given conservative treatments. Early treatments included closed chest drainage, and irrigation with normal saline by the patients’ swallowing. At the same time were given intravenous nutrition. When the patients’ conditions were improved, three cases were given nutrition through nasogastric tube at the same time. The remaining seven cases were given jejunostomy and were given nutritional support through vein and nutrient canal placed into the jejunum. Results: In the fi rst 3 patients, who were given emergency operative treatments, two cases died, only single case (33%) recovered. In the other ten cases, one case gave up treatment and discharged from hospital (died of infection with multiple organ failure after discharge). One case had encapsulated pyothorax with atelectasis after chest drainage, and the healing of esophagus rupture were infl uenced, so at the 25th day after esophageal rupture, pyothorax removal and repair of esophageal rupture were implemented, and the patient was recovered well after surgery. The rest eight cases were recovered well after closed chest drainage treatment (80%) without surgery. Conclusion: For the treatment of spontaneous esophageal rupture, we think that it should be given priority to conservative treatment. With adequate drainage and irrigation, and keeping balance of nutritional condition and water-electrolyte, a good therapeutic effect can usually be achieved. Asian Journal of Medical Sciences Vol. 7(3) 2016 89-93